ANTIFUNGAL EXTRACT ACTIVITYOF ISOLATE Nocardia sp. ATS-4.1 AGAINST Candida albicans InaCC-Y116 - Abdullah Abdullah; Rahmawati Rahmawati; Rikhsan Kurniatuhadi (BERITA BIOLOGI, 2020)
Candida albicans is a microorganism that knows as caused of candidiasis. Nocardia is known to have the ability to produce antifungal bioactive compounds to overcome cases of fungal infections. This research aims to determine the presence of antifungal activity and the good concentration from crude extract of Nocardia sp. ATS-4.1 to inhibit C. albicans InaCC-Y116 and. Antifungal activity test of isolate Nocardia sp. ATS-4.1 was performed using a well diffusion method on Mueller Hinton Agar (MHA) media with a concentration of 92%, 94%, 96%, 98%, 100% and nystatin (positive control) 0,0125% and DMSO 10% (negative control) incubated at 37 ᵒC for 24-48 hours. The results showed that the extract of Nocardia sp. ATS-4.1 can inhibit the growth of C. albicans. Nocardia sp. ATS-4.1 isolate extract concentration of 96% with a resistance diameter of 13.63 ± 0.53 mm with a strong category against the growth of  C. albicans InaCC-Y116.